2011
DOI: 10.1063/1.3589568
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of the blank shape for micro deep drawing of rectangular parts

Abstract: In this investigation the blank shape for micro deep drawing of rectangular parts was for the first time optimized using FEM method with consideration of the real process conditions in micro forming, i.e. the coefficient of friction and the flow curves of thin foils. The acquired optimized blank shape was then validated by applying it to experiments. For both numerical and experimental investigations a punch with a section of 2 x 1 mm 2 was used. Aluminum Al99.5 with a sheet thickness of 20 µm was used as blan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…This effect has a fundamental influence on the shape of the final deep drawn part. In [Hu11] it is shown that, if the material model and friction coefficient are adjusted to the actual condition in the micro range, it is possible to determine the optimal blank shape in a size-dependent FEM simulation and accordingly produce near net shaped parts in rectangular micro deep drawing, as shown in Fig. 2.55.…”
Section: Deep Drawing Of Rectangular Partsmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect has a fundamental influence on the shape of the final deep drawn part. In [Hu11] it is shown that, if the material model and friction coefficient are adjusted to the actual condition in the micro range, it is possible to determine the optimal blank shape in a size-dependent FEM simulation and accordingly produce near net shaped parts in rectangular micro deep drawing, as shown in Fig. 2.55.…”
Section: Deep Drawing Of Rectangular Partsmentioning
confidence: 99%
“…Using Al99.5, rectangular parts with no remaining flange can be formed. In [Hu11] these findings can be transferred to blanks made of E-Cu58 and 1.4301. The influence of tool geometry deviation on the punch force in rectangular micro deep drawing has been investigated in Behrens et al [Beh15].…”
Section: Deep Drawing Of Rectangular Partsmentioning
confidence: 99%